Perceived stress, trust, safety and severity of SARS-CoV-2 infection among patients discharged from hospital during the COVID-19 pandemic’s first wave: a PREMs survey - Henk Verloo; Eric Bonvin; Nadine Tacchini-Jacquier; Sevrine Monnay (BMJ Open)
Aim To investigate experiences of stress, feelings of safety, trust in healthcare staff and perceptions of the severity of a SARS-CoV-2 infection among inpatients discharged from Valais Hospital, Switzerland, during the COVID-19 pandemic’s first wave.Methods Discharged patients aged 18 years or more (n=4665), hospitalised between 28 February and 11 May 2020, whether they had been infected by SARS-CoV-2 or not, were asked to complete a self-reporting questionnaire, as were their informal caregivers, if available (n=866). Participants answered questions from Cohen’s Perceived Stress Scale (PSS) (0=no stress, 40=severe stress), Krajewska-Kułak et al’s Trust in Nurses Scale and Anderson and Dedrick’s Trust in Physician Scale (10=no trust, 50=complete trust), the severity of a SARS-CoV-2 infection (1=not serious, 5=very serious), as well as questions on their perceived feelings of safety (0=not safe, 10=extremely safe).Results Of our 1341 respondents, 141 had been infected with SARS-CoV-2. Median PSS score was 24 (IQR1–3=19–29), median trust in healthcare staff was 33 (IQR1–3=31–36), median perceived severity of a SARS-CoV-2 infection was 4 (IQR1−3=3–4) and the median feelings of safety score was 8 (IQR1–3=8–10). Significant differences were found between males and females for PSS scores (p<0.001) and trust scores (p<0.001). No significant differences were found between males and females for the perceived severity of SARS-CoV-2 infection scores (p=0.552) and the feelings of safety (p=0.751). Associations were found between age and trust scores (Rs=0.201), age and perceived SARS-CoV-2 severity scores (Rs=0.134), sex (female) and perceived stress (Rs=0.114), and sex (female) and trust scores (Rs=0.137). Associations were found between SARS-CoV-2 infected participants and the perceived SARS-CoV-2 severity score (Rs=−0.087), between trust scores and feelings of safety (Rs=0.147), and perceived severity of a SARS-CoV-2 infection (Rs=0.123).Discussion The results indicated that inpatients experienced significant feelings of stress regarding perceived symptoms of the illness, yet this did not affect their feelings of safety, trust in healthcare staff or perception of the severity of SARS-CoV-2 infection. Future patient-reported experience measures research is needed to give a voice to healthcare users and facilitate comparison measures internationally.